A New Single-Switch ZCS Flyback-Forward Converter with High Power Density. Issue 5 (3rd September 2022) - Jahangiri, Shahrzad; Delshad, Majid; Vesali, Mahmood
Abstract : In this paper, a new zero current switching flyback-forward DC-DC converter is proposed. In the proposed converter to provide soft switching condition, an auxiliary circuit without any additional switch is used, which increases the efficiency. In this converter the switch is gated with PWM signal; therefore, the design and implementation of the control circuit is simple. The other advantages of the proposed converter are elimination of the core reset circuit and power transfer to the output in turn on and turn off switch that cause to increase power density. The experimental results verified the theoretical analysis and the efficiency of the proposed converter in full load is about 93%.